Historiography - Winks, Robin W. (Oxford University Press, 1999)
Topics in this vein include the pressure of current events, access to primary sources, the creation of relevant university chairs, the rise of nationalism in former colonies, decolonization, and the Cold War. The chapters aim to demonstrate how the study of empire has evolved from a narrow focus on constitutional issues to a wide-ranging, multi-faceted analysis of international relations, the uses of power, and the influences and counter-influences between settler groups and indigenous peoples